2017
DOI: 10.13057/biodiv/d180344
|View full text |Cite
|
Sign up to set email alerts
|

How trust influence social capital to support collective action in agroforestry development?

Abstract: Abstract. Qurniati R, Febryano IG, Zulfiani D. 2017. How trust influence social capital to support collective action in agroforestry development ?. Biodiversitas 18: 1201?. Biodiversitas 18: -1206. Trust is an important factor for strengthening social capital. Trust in forest community is achieved through collective action in small scale agroforestry. It was challenging process regards the low on social capital in communities. This study intended to analyse and explain how trust influences social capital in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
2
15
0
14
Order By: Relevance
“…According to Ariftia et al (2014), the direct utilization value of mangrove forest in Margasari is only 18% of the total economic value. The low use of mangroves could be a threat as Qurniati et al (2017a) revealed community surrounding the forest have limited capital, it could decrease the conservation effort by the community. The mangrove conservation effort should be equal to the sustainable utilization through developing mangrove-focused ecotourism.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ariftia et al (2014), the direct utilization value of mangrove forest in Margasari is only 18% of the total economic value. The low use of mangroves could be a threat as Qurniati et al (2017a) revealed community surrounding the forest have limited capital, it could decrease the conservation effort by the community. The mangrove conservation effort should be equal to the sustainable utilization through developing mangrove-focused ecotourism.…”
Section: Introductionmentioning
confidence: 99%
“…Kepercayaan merupakan salah satu karakteristik pertama yang harus terdapat pada sebuah kelompok (Harahap dan Herman 2017 Amelia et al (2019) bahwa masyarakat bergaul tanpa memandang suku dan tidak membatasi pergaulan dengan siapapun. Penelitian yang dilakukan oleh Qurniati et al (2017a) menjelaskan bahwa kesamaan dalam hubungan suku dan agama dapat memperkuat kepercayaan masyarakat seperti ikatan modal sosial. Kepercayaan antara anggota kelompok maupun pengurus akan mampu mempererat ikatan yang terjalin dalam kelembagaan gapoktan.…”
Section: Modal Sosial Kepercayaanunclassified
“…Modal sosial merupakan norma dan nilai bersama yang dibangkitkan oleh kepercayaan (trust), dimana trust merupakan dasar bagi sikap keteraturan, kejujuran, dan perilaku kooperatif yang muncul dari dalam sebuah komunitas masyarakat (Cahyono dan Adhiatma 2012). Aksi kolektif masyarakat dapat terfasilitasi oleh modal sosial dan memberikan pengaruh yang kuat pada proses peningkatan kesejahteraan sosial (Qurniati et al 2017a;. Apabila modal sosial kuat, maka hal tersebut dapat menjadi pertimbangan pemerintah dalam mendukung program pembangunan.…”
unclassified
See 1 more Smart Citation
“…Keterlibatan pemerintah tergolong dalam kategori partisipasi terapi. Kurangnya komunikasi antara pemerintah dengan anggota kelompok mengakibatkan peran pemerintah masih kurang diharapkan oleh masyarakat pada pengelolaan mangrove (Qurniati et al 2017b).…”
Section: Keterlibatan Pemerintah Dalam Pengelolaan Mangroveunclassified